Making fiscal space happen!: Managing fiscal policy in a world of scaled-up aid - Peter S. Heller; Menachem Katz; Xavier Debrun; Theo Thomas; Taline Koranchelian (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Debt relief and the scaling up of aid to low-income countries should allow for greater fiscal space for expenditure programmes to create long-term growth and lower poverty rates. But designing a suitable medium-term fiscal framework that fosters a sustainable delivery of better public services and infrastructure while maintaining a credible commitment to fiscal prudence confronts many challenges. This paper discusses what low income countries can do to shape fiscal policy frameworks that are ambitious in trying to absorb additional aid while still ensuring longer-term sustainability for government expenditure programmes and finances. It suggests what approaches can be used to manage the greater fiscal policy risks associated with a scaled up aid environment, including coordination with monetary policy. The paper also discusses what institutional changes are needed if donors and countries are to facilitate the implementation of a higher level of aid-financed spending programmes. – aid ; fiscal policy ; low income countries ; macroeconomic policy ; public financial management
Keywords: O11; O23; H39; 330; Finanzpolitik; Öffentlicher Haushalt; Entwicklungshilfe; Schuldenerlass; Entwicklungsländer